THE EFFICIENCY OF PROJECT BASED LEARNING FOR DEVELOPING STUDENTS’ DIGITAL LITERACY (Universitas Muhammadiyah Palembang, 2022)
AbstractA project-based learning is one of strategies that integrates theory with practice; the students are challenged to work in teams in order to develop a project. This study aimed to determine the efficiency of project-based learning for developing students’ digital literacy of reading at English Education Study Program of Universitas Muhammadiyah Palembang, Indonesia. This research was done through qualitative descriptive study without test hypotheses. The data was taken that included the data regarding from the efficiency of project-based learning for developing students’ digital literacy was reviewed from the students’ perspectives. The sample was 24 students and the class was second semester students in the reading learning process was reviewed from the student's perspectives. Collecting the research data by using instruments, those were observation and questionnaire. From the results of the questionnaire in this study, it indicated that the project-based learning strategy has a positive impact on student learning, motivation and performance in digital literacy of reading. This study finally revealed that the incorporation of project-based learning enables the creation of real-life experiences, so it showed that the efficiency of project-based learning for developing students’ digital literacy was declared good and effective.Keywords: Efficiency; Project-Based Learning; Digital Literacy.